HUBUNGAN ANTARA PENYAKIT INFEKSI DAN MALNUTRISI PADA ANAK 2-5 TAHUN - Betan, Yasinta; Hemcahayat, Monthana; Wetasin, Kanokwan (JURNAL NERS LENTERA, 2018)
Introduction: Malnutrition is still a public health issue in Indonesia. In order to achieve Millennium Development Goals’ (MDGs) target, Indonesian government has improved the strategies to reduce the prevalence of malnutrition in children under five years old to be 15.5% in 2015. However, the prevalence of malnutrition including underweight and stunting increased from 17.9% and 35.6% in 2010 to 19.6% and 37.2% in 2013. The aim of this study was to examine the relationship between infection diseases and malnutrition among children 2-5 years old. Method: A cross sectional design was used in this study. Population of the study was children 2-5 years old in Wulanggitang subdistrict, East Flores, East Nusa Tenggara. A total sample of this study was 250 children. Purposive sampling was used to select the participants. Data were collected by face-to-face interview with a questionnaire and anthropometric measurements of weight and height. Achi-square test with α≤ 0.05 was used to analyze the data. Results: This study revealed that out of 250 participants, 40.4% had malnutrition and 58.8% had diseases including diarrhea and/or acute respiratory infection in the past six months. The study also revealed that occurrence of infection diseases (χ² = 48.56, p